A comprehensive university at the heart of its communities: establishing a framework for engagement - Boughey, John Desmond (University of the Free State, 2015)
The thesis documents the construction of a coherent conceptual and practical framework in which to locate the quest to establish community engagement as a legitimate, feasible and viable undertaking in higher education alongside its more established and accepted counterparts of teaching and research, with particular focus on the University of Zululand (UNIZULU) – a rural-based comprehensive university with an urban footprint. The thesis begins with a brief outline of the national context of community engagement before moving on to a more specific description of the context and recent history of UNIZULU. Certain key concepts are then clarified. A statement of the research concern and objectives of the study is followed by an account of the theoretical framework and research perspective underpinning the thesis, and a description of the methodology employed in the research. Ethical considerations are noted. There then follows a brief indication of the scope and intention of each of the papers, and the rationale behind the order in which they appear in the thesis. This brief introductory section concludes with speculation on what the significance of this study might be. Paper 1, Notions of ‘community engagement’ appropriate to a Community-University Partnership Programme (CUPP) in a South African rural-based comprehensive university – Siyanibona!, seeks to tease out contested understandings of the notions of ‘identity’, ‘community’ and ‘engagement’. In so doing it explores three particular ideas, taken up in later papers, namely: the notion of ‘relationships of fate’ needing to transform into ‘partnerships of choice’; the link between the circumstances of a particular university’s birth, and its acceptance or otherwise of its responsibility to its locale; and the need for all stakeholders in the community-university engagement endeavour to know more about each other at a level deeper than simply the institutional or organisational. Paper 2, From pillars to people: Reconceptualising the integration of teaching, research and community engagement in higher education, addresses the struggle community engagement has faced in achieving par with higher education’s other core activities of teaching-and- learning and research in a way which chooses not to look at teaching, research and community engagement as activities or objects, but from the perspective of the individual stakeholders (staff, students and community members) engaged in those activities. The exploration of this idea picks up on the distinction between ‘relationships of fate’ and ‘partnerships of choice’ first articulated in Paper I and expands the concept of ‘engagement’ to encompass the relationships between staff and students (not just those between the university and community members), and discusses ways in which staff, students and communities might more usefully interact with each other. Paper 3, SMMEs and higher education: Possibilities for partnership? homes in on a particular sector of the business community, to ascertain the extent to which the sector might be able to partner with the University to their mutual benefit. Using data from a questionnaire and interviews the study reveals that opportunities for work experience for students in micro and survivalist enterprises are limited but that the University could be doing more to ‘reach out’ to its communities by making them aware of who the university is, what it can offer, how it can assist, and perhaps most importantly, how it can be accessed. Paper 4, ProAct: An integrated model of action research and project management for capacitating universities and their communities in the co-production of useful knowledge, tells the story of the evolution of a hybrid model of action research and project management (ProAct) which takes account of the need for research in the university-community context to be accomplished democratically, but within specific parameters of time and other resources by grafting selected project management tools onto the basic action research cycle. The model gives practical and concrete form to the conceptual and theoretical constructs of other researchers who have considered the linking of action research and project management. Paper 5, A comprehensive university and its local communities: Establishing a framework for engagement, addresses the overarching question of how to establish a framework for engagement between a university and its communities. The paper employs the well-used ‘building construction’ metaphor, identifying the management and governance building blocks (including institutional self-identity, unequivocal support from institutional executive leadership, plans, policies, structures, and funding), and the ‘cement’ for holding the framework together (including familiarity with communities and knowing how to interact with them, changing mindsets and building capacity). The paper offers the opinion that the necessary foundation for the edifice is the institutional belief that engaging with communities is actually an integral and enhancing enabler of the higher education learning experience, not something which one is empowered to do after having been prepared exclusively in the lecture hall. The paper avers that if an institution does not come close to holding the view that the purpose of higher education is to provide something useful to society, starting with the communities that surround them, community engagement will always struggle to be accepted by the academy. In considering the significance of this whole study the thesis identifies the key ‘realisations’ which have given food for thought and which other researchers might find worthwhile exploring further too. These are: the significance of how institutional and community identities are established, by choice, fate or fiat; re-thinking the concept of ‘engagement’ to focus not on the activities per se of teaching, research and community engagement but on all of the stakeholders working as willing partners; the need for institutions and communities to embrace the belief that university-community interaction is one of the purposes of higher education, and the belief that community engagement is a vehicle for staff, student, curriculum and institutional development. In concluding, the thesis additionally notes the significance to the author himself of having taken this research journey. As a consequence he feels he is in a better position to promote a more integrated model of teaching, research and community engagement to his university, community colleagues, students, and community engagement peers in other universities. However, the author indicates that in furthering the cause of community engagement in higher education he will need to explore alternative paradigms, notably complexity science, and systemic action research.

In hierdie tesis is die konstruksie van ‘n samehangende konseptuele en praktiese raamwerk gedokumenteer, waarbinne die strewe om gemeenskaps-betrokkenheid as ‘n legitieme, haalbare en lewensvatbare onderneming in hoër onderwys, tesame met die meer gevestigde en aanvaarde gelyke vennote, onderrig en navorsing, te vestig. Die fokus is spesifiek op die Universiteit van Zoeloeland (UNIZULU) – ‘n landelike, komprehensiewe universiteit met ‘n stedelike voetspoor. Die tesis skop af met ŉ bondige oorsig van die nasionale konteks van gemeenskapsbetrokkenheid voordat daar oorgegaan word na ŉ meer spesifieke beskrywing van die konteks en onlangse geskiedenis van UNIZULU. Bepaalde sleutelkonsepte word daarna uitgeklaar. ŉ Stelling aangaande die navorsingsprobleem en doelwitte van die studie word gevolg deur ŉ weergawe van die teoretiese raamwerk en navorsingsperspektief onderliggend aan die tesis, asook ŉ beskrywing van die metodologie wat in die navorsing gebruik is. Etiese oorwegings word vermeld. Dan volg ŉ kort beskrywing van die omvang en doel van elk van die referate, en die rasionaal vir die volgorde waarin hulle in die tesis verskyn. Hierdie kort inleidende afdeling word afgesluit met ŉ bespiegeling oor wat die belang van die studie mag wees. Referaat 1, Gedagtes oor ‘gemeenskapsbetrokkenheid’ soos toepaslik in ŉ Gemeenskap- Universiteit-Vennootskapsprogram (GUVP) in ‘n Suid-Afrikaanse landelike komprehensiewe universiteit – Siyanibona!, poog om omstrede wyses waarop die idees van ‘identiteit’, ‘gemeenskap’ en ‘betrokkenheid’ verstaan word, uit te pluis. In die proses word drie spesifieke idees, wat in latere referate onder die loep kom, ondersoek, naamlik die idee van ‘lotsverhoudings’ wat in ‘vennootskappe van keuse’ moet verander; die verband tussen die omstandighede waaronder ŉ bepaalde universiteit in die lewe geroep is en die aanvaarding al dan nie van die verantwoordelikheid teenoor sy lokaliteit; en die nodigheid dat almal wat belang het by die strewe na betrokkenheid tussen gemeenskap en universiteit op ŉ dieper vlak as bloot die institusionele of organisatoriese meer van mekaar te wete te kom. Referaat 2, Van steunpilare na mense: Herkonseptualisering van die integrasie van onderrig, navorsing en gemeenskapsbetrokkenheid in hoër onderwys, skenk aandag aan die stryd wat gemeenskapsbetrokkenheid moes voer om op gelyke voet te kom met die ander kernaktiwiteite van hoër onderwys, naamlik onderrig-leer en navorsing, op ŉ wyse waar onderrig, navorsing en gemeenskaps-betrokkenheid nie as aktiwiteite of voorwerpe beskou word nie, maar vanuit die perspektief van die individuele belanghebbendes (personeel, studente en gemeenskapslede) betrokke by daardie aktiwiteite. Die verkenning van hierdie idee raak weer die onderskeid tussen ‘lotsverhoudings’ en ‘vennootskappe van keuse’ aan wat aanvanklik in Referaat 1 bespreek is, en brei die konsep van ‘betrokkenheid’ uit om die verhoudings tussen personeel en studente in te sluit (nie net dié tussen die universiteit en die gemeenskapslede nie), en bespreek wyses waarop personeel, studente en gemeenskappe op meer nuttige wyses met mekaar in wisselwerking kan tree. Referaat 3, KMMOs en hoër onderwys: Moontlikhede vir vennootskap? is afgestem op ŉ bepaalde sektor in die sakegemeenskap om die mate te bepaal waartoe die sektor in staat mag wees om ŉ vennootskap met die universiteit aan te gaan tot wedersydse voordeel. Uit data ingesamel deur middel van ŉ vraelysondersoek en onderhoude maak die studie dit duidelik dat geleenthede vir werkervaring vir studente in mikro- en oorlewingsondernemings beperk is, maar dat die universiteit meer kan doen om ‘uit te reik’ na sy gemeenskappe deur hulle bewus te maak van wie die universiteit is, wat dit kan bied, hoe dit hulp kan verleen, en, miskien die belangrikste, hoe toegang tot die universiteit verkry kan word. Referaat 4, ProAct: ‘n Geïntegreerde model van aksienavorsing en projekbestuur om universiteite en hul gemeenskappe in staat te stel om die gesamentlike produksie van nuttige kennis te verwesenlik, vertel die verhaal van die evolusie van ŉ hibriede model van aksienavorsing en projekbestuur (ProAct) wat in ag neem dat daar ŉ behoefte aan navorsing bestaan in die universiteit-gemeenskapskonteks, waaraan op demokratiese wyse voldoen moet word, maar wel binne die spesifieke parameters van tyd en hulpbronne deur geselekteerde projekbestuursinstrumente op die basiese aksienavorsingsiklus oor te dra. Hierdie model gee praktiese en konkrete vorm aan die konseptuele en teoretiese konstrukte van ander navorsers wat oorweging skenk aan die koppeling van aksienavorsing en projekbestuur. Referaat 5, ŉ Komprehensiewe universiteit en sy plaaslike gemeenskappe: Die vestiging van ŉ raamwerk vir betrokkenheid, gee aandag aan die oorkoepelende vraag van hoe om ŉ raamwerk vir betrokkenheid tussen ŉ universiteit en sy gemeenskappe te vestig. Die referaat benut die welbekende metafoor van ‘boukonstruksie’, waarvolgens die bestuurs- en beheerboublokke (insluitend institusionele self-identiteit, onomwonde ondersteuning van institusionele uitvoerende leierskap, planne, beleide, strukture en befondsing), en die ‘sement’ wat die raamwerk bymekaar moet hou (insluitend ingeligtheid rakende gemeenskappe en hoe om met hulle in interaksie te tree, veranderende ingesteldhede, en kapasiteitsbou) geïdentifiseer word. Die referaat spreek die mening uit dat die nodige fondasie vir die gebou die institusionele oortuiging is dat om by gemeenskappe betrokke te raak in werklikheid ŉ integrale en versterkende bemagtiger van leerervarings in hoër onderwys is, nie iets wat ŉ mens bemagtig is om te doen nadat jy uitsluitlik in die lesingsaal voorberei is nie. Die referaat verklaar dat indien ŉ instelling nog nie naby die siening kom dat dit die doel van hoër onderwys is om iets nuttig aan die gemeenskap te voorsien nie – beginnende by die gemeenskappe reg rondom hulle – sal gemeenskapsbetrokkenheid altyd ŉ stryd voer om deur die akademie aanvaar te word. Wanneer die veelseggendheid van hierdie studie in oënskou geneem word, identifiseer die tesis die sleutel-‘bewuswordings’ wat stof tot nadenke was en wat ander navorsers ook die moeite werd mag ag om verder te ondersoek. Dit sluit in dat dit betekenisvol is hoe institusionele en gemeenskapsidentiteite gevestig word, deur keuse, die noodlot of op bevel; herbesinning oor die konsep van ‘betrokkenheid’ sodat daar nie op die onderrig-, navorsings- en gemeenskaps-betrokkenheidsaktiwiteite per se gefokus word nie, maar op al die belanghebbendes wat as gewillige vennote werk; die noodsaaklikheid daarvan dat instellings en gemeenskappe wesenlik oortuig is dat universiteit-gemeenskap-interaksie een van die doelwitte van hoër onderwys is; en die oortuiging dat gemeenskapsbetrokkenheid ŉ medium is vir personeel-, studente-, kurrikulum- en institusionele ontwikkeling. Ten slotte dui die tesis ook die betekenis wat die navorsingsreis vir die navorser self ingehou het, aan. As gevolg hiervan voel hy dat hy beter toegerus is om ŉ geïntegreerde model van onderrig, navorsing en gemeenskapsbetrokkenheid by sy universiteit, gemeenskapskollegas, studente en eweknieë in gemeenskapsbetrokkenheid aan ander universiteite te bevorder. Die skrywer dui egter aan dat om die saak van gemeenskapsbetrokkenheid verder te bevorder in hoër onderwys sal hy alternatiewe paradigmas moet ondersoek, veral kompleksiteitswetenskap en sistematiese aksienavorsing.
Thesis (Ph.D. (School of Higher Education Studies))--University of the Free State, 2014
Keywords: Universities and colleges -- South Africa -- KwaZulu-Natal; Community and colleges -- South Africa -- KwaZulu-Natal